Talocalcaneocentral luxation combined with lateral instability of the talocrural joint in a dog and a cat - Hurter, K.; Schawalder, P.; Schmökel, H. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Tarsal injuries occur commonly in the cat and the dog, often due to motor vehicle accidents. In two cases a talocalcaneocentral luxation was associated with lateral talocrural instability. The surgical fixation of the talocalcaneocentral luxation, employing Kirschner pins in a cat and a DC plate in a dog, together with stabilisation of the lateral talocrural joint resulted in good long-term healing. The main aim of the surgical techniques used in these two cases was to stabilise the joints, without crossing and immobilising the talocalcaneal joint.
Keywords: Talocalcaneocentral luxation; tarsus; dog; cat